PENGARUH STRES KERJA, WORK LIFE BALANCE, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOMANEKA AT RASA SAYANG, UBUD - I Gusti Putu Bagus Kartika Putra; Ni Wayan Sukartini; Kadek Jemmy Waciko (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the partial and simultaneous effects of work stress, work-life balance, and work environment on employee performance. The research was conducted at Komaneka at Rasa Sayang. The population consisted of all employees at Komaneka at Rasa Sayang, with a sample of 65 respondents. The data analysis techniques used in this study included validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation analysis, coefficient of determination test, F-test, and t-test. The results indicate that work stress has a significant negative effect on employee performance, while work-life balance and work environment have significant positive effects on employee performance. Simultaneously, work stress, work-life balance, and work environment significantly affect employee performance. Based on these findings, it is recommended that Komaneka at Rasa Sayang, Ubud, ensure employees have adequate rest time during work hours, establish clear working hour policies, provide complete and well-maintained facilities, and regularly offer training programs to enhance employee capabilities in achieving the company’s performance targets.